Assessing the Overlap in Dating Violence Perpetration and Victimization among South Korean College Students: The Influence of Social Learning and Self-Control - Jennings, Wesley G. (American journal of criminal justice, 2011)
Research has recently begun to identify an overlap of involvement in offending and victimization and a shared commonality of risk factors for both outcomes. Despite this growing body of evidence, this research has yet to have been extended to dating violence in general and in cross cultural samples specifically. Recognizing these gaps in the literature, the current study examines the correlation between psychological and physical dating violence perpetration and victimization among a large sample of South Korean college students. Results from a series of bivariate probit models suggest that there is a strong degree of overlap between dating violence perpetration and victimization and that social learning theory and self-control theory cannot explain away the overlap. Study limitations and implications are also discussed.